Keputusan Hakim Dalam Pemberian Dispensasi Nikah Di Pengadilan Agama Kota Pati - Syahrul Rizqi Ramadhan; Dania Maulinda; Tarisa Dinar Alifia; M. Bondhi Alby Maulana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Applications for dispensation have increased in recent years in various cities. This happened because of changes to Law no. 1 of 1974 which is considered too low and cause many problems in marriage. Therefore, in 2019 there were changes to the Marriage Law, namely Law no. 16 2019 aims to be an effort to mature in age marriage for women from 16 years to 19 years. One of them is the marriage dispensation at the religious court in Pati City. Applications for marriage dispensations in the city of Pati have increased very drastically. The type of research used by the author is normative law. By using a legal approach and norms that apply in society. The results of research conducted by the author on requests for marriage dispensation. There are factors causing the ineffectiveness of these regulations in the Pati Religious Court, namely the lack of socialization to the community, public awareness, there is still an increase in cases of requests marriage dispensation. Factors that encourage the increase in application cases Marriage dispensations include factors such as social media, environment, pregnancy outside.